Keywords Assigned by Scientific Authors as an Indexing Element: A Comparative Study of Representation - da Silva Mota de Souza, Cláudia Santos; Redigolo, Franciele Marques [UNESP]; Fujita, Mariângela Spotti Lopes [UNESP]; Gil-Leiva, Isidoro (Nomos Verlag, 2024)
The choice of keywords by an author aims to represent the content of scientific texts. To verify authors' keyword consistency in the area of Information Science in articles and on their Lattes Platform, the objective of this investigation was to analyze the keywords assigned in the articles from the journal Ciência da Informação and compare them with those assigned by the authors on their Lattes Platform. Carried out a theoretical study on “keywords as an indexing element,” collected keywords from authors' journal articles and from their Lattes Platform, and analyzed the keywords in authors' journal articles comparing them with those registered on their Lattes Platform. Findings reveal a low correlation between the keywords assigned by the authors in the articles and the keywords registered on their Lattes Platform. Concluded that there is no indexing policy for keywords' representation on scientific databases.